Population-specific FST values for forensic STR markers: A worldwide survey. (July 2016) - Buckleton, John; Curran, James; Goudet, Jérôme; Taylor, Duncan; Thiery, Alexandre; Weir, B.S.
Abstract : Highlights: Largest survey of published frequencies of forensic STR alleles. Clarification of meaning of F ST needed to calculate match probabilities. Demonstration that F ST can be expressed in terms of allelic matching proportions within and between populations. Demonstration that F ST for a population depends on the set of populations to which it is compared. Abstract: The interpretation of matching between DNA profiles of a person of interest and an item of evidence is undertaken using population genetic models to predict the probability of matching by chance. Calculation of matching probabilities is straightforward if allelic probabilities are known, or can be estimated, in the relevant population. It is more often the case, however, that the relevant population has not been sampled and allele frequencies are available only from a broader collection of populations as might be represented in a national or regional database. Variation of allele probabilities among the relevant populations is quantified by the population structure quantity F ST and this quantity affects matching proportions. Matching within a population can be interpreted only with respect to matching between populations and we show here that F ST, can be estimated from sample allelic matching proportions within and between populations. We report such estimates from data we extracted from 250 papers in the forensic literature, representing STR profiles at up to 24 loci from nearly 500, 000 people in 446 different populations. The results suggest that theta values in current forensic use do not have the buffer of conservatism often thought.